2015
DOI: 10.1179/1743133615y.0000000009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tin on microstructure and mechanical properties of compacted graphite iron

Abstract: This experiment investigated the effect of tin in an amount up to 0?121 wt-% on the microstructure and mechanical properties of compacted graphite iron. Graphite and matrix evolution was emphasised with the help of scanning electron microscopy. The results indicate that Sn in experimental range reduces graphite size. Pearlite quantity would increase with the increasing Sn and reaches over 95% when Sn is .0?057 wt-%. Sn helps to narrow the lamellar spacing of pearlite from sorbitic pearlite (320 nm) to troostit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This would lead to an increase in the interlamellar spacing for given casting conditions and cooling rate and thus to a decrease in micro-hardness close to graphite precipitates. Note that this explana tion would apply to fully pearlitic matrix and not to cast irons containing some ferrite located around graphite precipitates as in the recent work by Liu et al [21]. This suggestion would be worth dedicated experiments involving isothermal growth of pearlite after austenitization.…”
Section: Resultsmentioning
confidence: 90%
“…This would lead to an increase in the interlamellar spacing for given casting conditions and cooling rate and thus to a decrease in micro-hardness close to graphite precipitates. Note that this explana tion would apply to fully pearlitic matrix and not to cast irons containing some ferrite located around graphite precipitates as in the recent work by Liu et al [21]. This suggestion would be worth dedicated experiments involving isothermal growth of pearlite after austenitization.…”
Section: Resultsmentioning
confidence: 90%
“…Usually, during eutectic reaction, carbon atoms continuously move from austenite to graphite and leave a C-lack area around graphite, which will finally become ferrite. Lyu et al [19] demonstrated that Sn tends to exist at the boundary between graphite and austenite during eutectic reaction, obstructing the C transfer. Consequently, the areas close to vermicular graphite contained enough C atoms to form pearlite.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, alloying is likely to be an easy way to improve the properties of CGI. Copper, titanium, and tin were found to be effective in increasing the strength of CGI by promoting the formation of pearlite [17][18][19], but the influences of these alloys to the wear resistance of CGI is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Shaban et al showed that tin (Sn) increased compact graphite and graphite aspect ratio [9]. In their study in vermicular cast iron, Lyu et al found out that graphite size clearly decreased as tin (Sn) content increased between 0.003 and 0.057% by weight and an increase in tensile strength and impact toughness was obtained [10]. In a study on nodular cast iron by Lacaze et al, it's determined that tin rate was harmful after 0.05% [11].…”
Section: Introductionmentioning
confidence: 99%